Incentivos regulatórios para investimentos em infraestrutura: Opç\~oes reais e a metodologia de indenizaç\~ao de ativos - Katia Rocha; Naielly Lopes Marques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study explores how the design of regulatory incentives proposed by the granting authority has the potential to impact the concessionaire's investment decisions regarding participation in the bidding process, the potential value of grants and the request for a re-bidding process or concession devolution. Such incentives intrinsically embody contingent values similar to those of a Real Option. The proposed model analyzes the investment option in a typical concession (call), from which we investigate the impacts of the Lei das Relicitaç\~oes and the concession devolution (put) under different indemnification methodologies of investments linked to non-depreciated or amortized reversible assets on the behavior of investors (redemption payoff). It is a type of compound option (a call of a put). The results clearly illustrate the tradeoff between the attractiveness of the concession and compensation policy. The adoption of indemnification methodologies that result in higher values - historical cost or new replacement value, to the detriment of fair market value - implies greater incentive to participate in the bidding process, greater potential for grants and better attractiveness of the concession itself. The greater the demand uncertainty, the greater the investor's aversion to participating in the event, requiring high demand to commit to investments, and supporting greater demand frustration before the concession devolution - hysteresis region. By including penalties for the exercise of devolution, the proposed model allows analyzing compensation policies to stimulate the attractiveness of concessions and also discuss ways to discourage opportunistic devolution behavior. The results serve as a point of attention for the public policy maker and regulator, especially in the structuring of projects and analysis of regulatory impacts of unattractive concessions and PPPs - low NPV or with high demand uncertainty, precisely where the real options methodology produces greater impact by leveraging investments. We emphasize that the best design may not be the one that exempts the government, but rather the one that makes the project viable.
10419/284894
Keywords: L51; L9; L98; 330; concessions and PPPs; Lei das Relicitaç\~oes; methodologies of calculation on indemnification of investments; real options